Ответ:
Объяснение:
(х+1)²=(2х-1)²
х²+2х+1=2х²-4х+1
х²-6х=0
х(х-6)=0
х1=0 х2=6
2)(2х-3)²=11х-19
4х²-12х+9=11х-19
4х²-23х+28=0
D=(-23)²-4×28×4=529-448=81
x1=23+9/8=4 x2=23-9/8=7/4
3)15(x+1)²=15x²+17
15(x²+2x+1)=15x²+17
15x²+30x+15=15x²+17
30x=2
x=1/15
4)(x-2)²=-2x+31
x²-4x+4=-2x+31
x²-2x-27=0
D=(-2)²-4×(-27)=4+108=112
x1=2+/112/2 x2=2-/112/2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
(х+1)²=(2х-1)²
х²+2х+1=2х²-4х+1
х²-6х=0
х(х-6)=0
х1=0 х2=6
2)(2х-3)²=11х-19
4х²-12х+9=11х-19
4х²-23х+28=0
D=(-23)²-4×28×4=529-448=81
x1=23+9/8=4 x2=23-9/8=7/4
3)15(x+1)²=15x²+17
15(x²+2x+1)=15x²+17
15x²+30x+15=15x²+17
30x=2
x=1/15
4)(x-2)²=-2x+31
x²-4x+4=-2x+31
x²-2x-27=0
D=(-2)²-4×(-27)=4+108=112
x1=2+/112/2 x2=2-/112/2